Strategi Inovatif Pengelolaan Wisata BUMDes Desa Pudun Jae Kota Padangsidimpuan - Poppy Honora; Asmul Fauzi Harahap; Muhammar Syafii; Edison Siregar (CV. ITTC INDONESIA, 2026)
The development of tourism based on Village-Owned Enterprises (BUMDes) has become an important strategy for strengthening local economic independence through the optimization of village potential. This study aims to analyze innovative strategies for managing BUMDes tourism in Pudun Jae Village, Padangsidimpuan City, and to identify supporting and inhibiting factors in its development. This research employed a qualitative approach with a descriptive method. Data were collected through observations, in-depth interviews, and documentation, followed by data analysis through data reduction, data presentation, and conclusion drawing. The findings indicate that innovative tourism management strategies require institutional strengthening, improvement of managerial capacity, development of local-based tourism products, utilization of digital technology, and active community participation. These strategies are expected to enhance tourism competitiveness while supporting sustainable economic and social development for the community of Pudun Jae Village.